UPAYA TERTIB LISTRIK TERHADAP INSTALATIR KABEL DI DAERAH PADAT PENDUDUK (STUDY KASUS KEC. TAMBORA) - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
Electricity is a very important thing in everyday life, in the absence of electricity all things related to this heat energy will experience obstacles. The densely populated residential area located in Tambora Village, Kosambi District, West Jakarta, are a targeted area for an orderly area of electricity, where some of its people illegally stole electricity. This is very dangerous for users or harm PLN, for that criminal effort must be eradicated through the extension program or orderly socialization in order not to cause a fire. The method used is observation in the area of tambora village by looking at the connection installation used. The objectives of the program of orderly electricity socialization are: to give understanding to the people of Tambora Village due to electrical locking (stolen) and electrical installer failure of fire hazard due to short circuit.